2005
DOI: 10.1889/1.2137632
|View full text |Cite
|
Sign up to set email alerts
|

High-luminous-efficacy structure for plasma tubes

Abstract: Abstract— The plasma‐tube‐array display is expected to become a wall‐sized display with very high luminous efficacy. The cell design for high luminous efficacy was investigated. Also, discharging in the plasma tube was observed in order to investigate the structure for high luminous efficacy. As the result, a high luminous efficacy of 5.4 lm/W was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…At Fujitsu Laboratories, the luminous efficacy of 3.7 lm/W has been obtained by adding a high-voltage part in the front edge of sustain pulse [16]. Fujitsu Laboratories also reported 4.7 lm/W in the plasma tube which has three times the cell size of conventional PDPs and the design of sustain gap 0.4 mm [17], [18].…”
Section: B Technologies For High Luminous Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…At Fujitsu Laboratories, the luminous efficacy of 3.7 lm/W has been obtained by adding a high-voltage part in the front edge of sustain pulse [16]. Fujitsu Laboratories also reported 4.7 lm/W in the plasma tube which has three times the cell size of conventional PDPs and the design of sustain gap 0.4 mm [17], [18].…”
Section: B Technologies For High Luminous Efficacymentioning
confidence: 99%
“…Since the manufacturing unit is one glass tube, it can manufacture the small equipment and facilities for production. Since pixel size is large, about three times compared with the conventional PDPs, high luminous efficacy is theoretically expected [18]. So, even if it forms extra-large screen, the increase in power consumption can be suppressed.…”
Section: Technical Trend Of Enlargement Of Pdpmentioning
confidence: 99%
“…Looking for general trends, it is concluded that phosphor saturation induces a substantial decrease in the efficacy in all cases with the exception of this work, where a special phosphor is applied, and Ref. 24, where the luminance level is such that phosphor saturation is not significant. The resemblance of the discharge physics for all these designs may be larger than expected at first sight, since a high sustain voltage presumably increases the discharge efficiency in all cases.…”
Section: Comparison Of High-efficacy Pdp Designsmentioning
confidence: 73%
“…Thus, for comparison, the effective Xe content of the low-pressure case, Ref. 24 in Table 2, can be taken as roughly halve the tabulated value. Thirdly, according to the above, the initial phase of the discharge is more efficient.…”
Section: Comparison Of High-efficacy Pdp Designsmentioning
confidence: 99%
“…With the rectangular tube, the distance between discharge and the phosphor were closer and the solid angle from discharge to the phosphor layer is larger. With a 10% Xe discharge gas mixture, high luminous efficacy of 5.4 lm/W was achieved [3] .…”
Section: Fig4 Rectangular Tube and Luminous Efficacymentioning
confidence: 98%